Essays on financial frictions, collateral and default - Romanidis, N (2020)
The first model of my thesis introduces a monetary Real Business Cycle model with incomplete markets, a durable good, collateralized securities and endogenous default. We establish that equilibria are inefficient since agents underinvest due to the existence of endogenous default. Moreover, the Pareto optimal equilibrium allocation cannot be achieved through monetary policy. Our analysis suggests the need of an additional policy tool to generate optimal investment and improve equilibrium allocations. In the second model of my thesis, we propose an integrated tractable framework that incorporates endogenous default in a continuous-time setting. Productive experts that face leverage constraints and aggregate risk, borrow from households and choose to partially default subject to a penalty that decreases their objective function. Our results show that default increases borrowing costs, lowers expert’s capital holdings, suppresses investment and subsequently leading to a recession. We show that the path of inflation under quantitative easing policies that target interest rates, is determinate in the presence of default. We achieve this through different payoff profiles that a collateralised defaultable bond achieves in different states of nature with distinct default outcomes. In the model, heterogeneous households trade this bond and other shorter maturity risk-free bonds to maximise their intertemporal utility of consumption and labour. The differentiated payoffs of the collateralised bond, in an equilibrium with active default, span the full state space giving determinacy of prices and inflation as an outcome.